ANALISIS KERENTANAN TANAH LONGSOR DI SUB DAS CEMORO DENGAN APLIKASI SISTEM INFORMASI GEOGRAFIS - Beny Harjadi; Alfiana Puspaningrum (Universitas Lambung Mangkurat, 2022)
Landslides in Bengawan Solo Watershed can be caused by the increasing area of critical land and continuous process of erosion. Landslides vulnerability also caused by the condition of slope that are sloping to steep, soil textures which tends to smooth and deep regolith. It can affect the activity of the community around the watershed. This study aims to analyze the level of landslides vulnerability in Cemoro sub-watershed as part of the Bengawan Solo Watershed in order to reduce the impact of landslides by using Geographic Information System. Landslides vulnerability is determined by considering factors such as geological type, soil regolith depth, slope, fault and soil texture. Based on the result of landslides vulnerability analysis, the Cemoro sub watershed has two levels of landslides vulnerability which are a low level of 68,17% with 658,4 ha of area and a medium level of 31,83% with 307,35 ha of area. Results of this study is a map of landslides vulnerability which is used as a reference to improve mitigation in the Cemoro sub watershed using soil conservation.